2003
DOI: 10.1186/1479-5876-1-14
|View full text |Cite
|
Sign up to set email alerts
|

The Granzyme B ELISPOT assay: an alternative to the 51Cr-release assay for monitoring cell-mediated cytotoxicity

Abstract: Background: The interferon-γ (IFN-γ) ELISPOT assay is one of the most useful techniques for immunological monitoring of cancer vaccine trials and has gained increased application as a measure of specific T cell activation. However, it does not assess cell-mediated cytotoxicity directly as IFN-γ secretion is not limited to only cytolytic cells. Granzyme B (GrB) is a key mediator of target cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…ELISpot granzyme B assays were used since this assay provides a measure of functional CTL activity [33,34]. We observed a significant increase in CTL activity after immunizations with Ad5 [E1-, E2b-]-CEA(6D) indicating that CEA specific CTL activity was induced.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…ELISpot granzyme B assays were used since this assay provides a measure of functional CTL activity [33,34]. We observed a significant increase in CTL activity after immunizations with Ad5 [E1-, E2b-]-CEA(6D) indicating that CEA specific CTL activity was induced.…”
Section: Discussionmentioning
confidence: 91%
“…An ELISpot assay for granzyme B-secreting lymphocytes to detect cytolytic T cell activity [33,34] was also performed. Briefly, isolated PBMC (2×10 5 cells/well) from individual patient samples were incubated 36–40 hours with a CEA peptide pool (15mers with 11aa overlap covering full length CEA with the CAP1-6D modification; 0.1 µg/well) to stimulate IFN-γ or granzyme B-secreting cells.…”
Section: Methodsmentioning
confidence: 99%
“…[32]. Briefly, cells from the HLA-A*02:01-positive T2 cell line were used as target cells and were loaded with pCMV_pp65_A02 and beta-2-microglobulin (Sigma-Aldrich) for 2 hours.…”
Section: Methodsmentioning
confidence: 99%
“…A strong correlation between Granzyme B and IFN-g ELISPOT assay with cytotoxicity in 51 Cr-release assay (R 2 D 0.95) was reported by Shafer-Weaver et al 39 In the ex vivo ELISPOT assay, which has been previously reported by Patil et al, 40 PBMCs were first incubated with 50 ng/ml of IL-7 and 10 ng/ml of IL-12 in culture medium for 2 h at 37 C. After incubation, the cells were washed with HBSS (Gibco, Life Technologies) and re-suspended at 5 £ 10 5 cells per well with complete culture medium containing RPMI (Gibco, Life Technologies) supplemented with 5% heat-inactivated human AB serum (Gemini Bio-Product) and 1£ penicillin/streptomycin (Gibco, Life Technologies) in a 96-well plate. Then, 50 mg/ml of peptides (appropriately selected depending on patient's HLAtype) was added to the respective wells and the cells were incubated overnight at 37 C and followed by ELISPOT assay as described below.…”
Section: Dendritic Cell Preparation and Stimulation Of T Cellsmentioning
confidence: 55%